Tadpoles of Rhinella schneideri as reservoirs of trichodinids in continental aquaculture - Pala, G. [UNESP]; Valladão, G. M.R. [UNESP]; Alves, L. O. [UNESP]; Pilarski, F. [UNESP]; Lux Hoppe, E. G. [UNESP] (Elsevier, 2018)
Restricted contact between wild amphibians and cultured fish facilitates the transmission of various diseases, including parasitic diseases. The trichodinids are one of the most important ectoparasites in fish farming in continental aquaculture, as they cause significant lesions in the integument and in the gills of the animals, causing mortality outbreaks. Thus the objective of this study is to describe the interaction between trichodinids and wild amphibians found in an earth pond prepared to receive fish from cultivation. Seventy five Rhinella schneideri tadpoles were collected for parasitological assessment. All studied tadpoles were severely parasitized by Trichodina heterodentata, with mean intensity and abundance of 7332 ± 3689.5 and range of intensity of 1394–13,240. Despite the high parasitism, no lesions were observed in the animals, mainly due to the large amount of mucus secreted under its integument, forming a protective layer. Wild amphibians are being found inside fish farming tanks, mainly because of the abundant availability of food, providing a calm and ideal environment for breeding. However, tadpoles are able to maintain high rates of parasitism by trichodinids, aiding in the dissemination of parasites to cultured fish. The present work reports for the first time this interrelationship between different species, sharing the same environment and pathogens, with potential damage to the health of commercial farmed hosts.
Keywords: Amphibians; Ectoparasites; Electron microscopy; Fish; Host–parasite relationship